1966
DOI: 10.1039/j19660000092
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity and molecular association. Part VI. Association of dihydric alcohols and phenols

Abstract: The physical properties of eleven alkanediols and two dihydric phenols have been determined, and their degrees of association estimated by an empirical relationship. The dependence on molecular structure of the apparent extent of association so deduced has been investigated, and the nature of the association complexes in the pure liquid state examined.FOR non-associated liquids, it has been shown that the of molecular size, shape, and polarity, the average value variation of liquid viscosity (q) with vapour pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…On the other hand, our data are in a good agreement with the latter authors at higher temperatures; over 380 K up to 460 K (mean average deviation less than 3 %). Above 400 K, the vapor pressures of 1,3-propanediol obtained in this work are in quite good agreement with Thomas and Meatyard values and in excellent agreement with Olson's data . In addition, the enthalpy of vaporization deduced from the experimental results is in a very good agreement with Knauth and Sabbah value determined using a calorimeter (within 1.2 kJ·mol –1 ), as in Table .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…On the other hand, our data are in a good agreement with the latter authors at higher temperatures; over 380 K up to 460 K (mean average deviation less than 3 %). Above 400 K, the vapor pressures of 1,3-propanediol obtained in this work are in quite good agreement with Thomas and Meatyard values and in excellent agreement with Olson's data . In addition, the enthalpy of vaporization deduced from the experimental results is in a very good agreement with Knauth and Sabbah value determined using a calorimeter (within 1.2 kJ·mol –1 ), as in Table .…”
Section: Resultssupporting
confidence: 88%
“…Relative deviation of the experimental vapor pressures of 1,3-propanediol from values obtained with the Antoine equation as a function of temperature T /K: ○, this work; △, ref ; +, ref ; ∗, ref ; □, ref ; ⧫, ref .…”
Section: Resultsmentioning
confidence: 93%
“…Except for the six hexanols and ethylene glycol, we have the present values therefore serve to extend the previous data previously recorded (14,15) the viscosities, at room temperature to lower temperatures. Although repeat measurements at and upward, of all the materials considered in the present work; overlap temperatures have not been conducted, numerical differentiation (see below) showed that in no case was there any discontinuity between our two sets of data.…”
Section: Methodssupporting
confidence: 85%
“…The physical properties of five (of the six) dihydric alcohol samples have also been previously recorded (15). In general, dihydric alcohols have not been as extensively studied as have the lower monohydric alcohols, but when comparisons can be made, agreement is again satisfactory; thus for propan-1,2-diol, propan-1,3-diol, and 2-methylpentan-2,4-diol, refractive indices at 20 °C agree with literature values to an average 0.0003.…”
Section: Methodsmentioning
confidence: 99%
“…The vapor pressures of (±)-1,2-propanediol (see table 1) were studied earlier [19][20][21][22][23][24][25][26], but no enthalpies of vaporization were derived from those literature data in the original works with the exception of Steele et al [24]. Equations (4) and (5) were applied in this work to each available experimental data set in order to obtain enthalpy of vaporization values and to provide a consistent comparison between literature results and the present work (table 1).…”
Section: Vapour Pressure and Vaporization Enthalpies Of 12-propanediolsmentioning
confidence: 99%